Turkmenistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in Turkmenistan during 1994-98. Turkmenistan reduced gas exports and suffered a decline in real GDP of close to 40 percent during 1993-95. At the same time, it stepped up foreign borrowing and constrained imports by limiting access to foreign exchange to sustain gross international reserves at the equivalent of 6-9 months of imports. The distortions associated with the perpetuation of central controls, coupled with an accommodating monetary policy, led to financial instability, raising annual average inflation rates to close to 1,500 percent during 1993-95.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet